"Dissecting Gonadoblastoma" of Scully: A Morphologic Variant That Often Mimics Germinoma. (October 2016) - Kao, Chia-Sui; Idrees, Muhammad T.; Young, Robert H.; Ulbright, Thomas M.
Abstract : Dr Robert E. Scully, who recognized and defined gonadoblastoma (GB), used the term "dissecting gonadoblastoma" (DGB) to describe variants with either an infiltrative type or diffuse pattern instead of the usual small nested arrangement. These patterns have not been emphasized in the literature. To investigate the features of DGB we examined 50 GBs microscopically and performed immunohistochemistry (IHC) in some. DGB was found in 38 (76%) GBs and was represented by 3 patterns. The most frequent was solid/expansile (n=26), consisting of large coalescent nests of germ cells, often (92%) interrupted by fibrovascular septa, with usually minor numbers of sex cord cells. Less frequent were small anastomosing nests (n=24) and cord-like arrangements (n=22) of germ cells irregularly distributed in a prominent stroma and with mostly inconspicuous sex cord cells. Most DGBs (24) showed >1 pattern and demonstrated the characteristic globular deposits of basement membrane, although these were often subtle. The germ cells in all patterns varied from spermatogonium-like to seminoma-like; OCT3/4 was positive only in the latter (7/7). The sex cord cells were small with dense, oval or angulated nuclei, inconspicuous nucleoli, and positivity for inhibin (9/9, strong), FOXL2 (9/9, strong), SF1 (8/9, strong), SOX9 (9/9, weak and focal), WT1 (5/7, variable), and calretinin (3/7, variable). Granulomas were present in 84% of germinoma foci, 13% of DGB foci, and 8% of classic GB foci. Twenty two of 38 DGBs had associated germinoma; 3 also had embryonal carcinoma, yolk sac tumor, and choriocarcinoma, respectively. Follow-up of 2 cases lacking an invasive tumor showed that both patients were disease free at 13 and 4.8 years after bilateral gonadectomy. We conclude that DGB is commonly seen with classic GB and displays identical IHC features, supporting it as a morphologic variant of GB. It appears likely that cord-like DGB is the earliest phase in a GB developmental continuum that may proceed successively into anastomosing, nested (classic GB), and solid/expansile patterns. DGB often mimics germinoma because of the large size of the nests, pseudoinfiltrative pattern of some cases, and inconspicuous sex cord cells. The presence of sex cord cells (identification aided by IHC for sex cord markers), the heterogenous morphology of the germ cells, and globules of basement membrane are useful differential features. The lack of a granulomatous reaction also favors DGB over germinoma. Mistaking DGB for GB with invasive germinoma may result in more aggressive therapy than warranted. The likely relationship of DGB to the relatively recently described concept of so-called "undifferentiated gonadal tissue" is discussed herein.